The Influence of QRIS Use and Utilization on Public Shopping Interest at Rambang Port, Pahandut District - Sucy, First; Viani, Griselda Okta; Kumalasari, Intan (Business Management, 2026)
This study aims to analyze the influence of QRIS usage on public shopping interest in the culinary area of Rambang Port, Pahandut District, and to understand the dynamics of consumer behavior through the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) approaches. The research method used is a quantitative approach by distributing questionnaires to consumers who transact in the area and data analysis using simple linear regression. The results show that the variables of ease of use, perceived security, and benefits of QRIS have a significant influence on increasing public shopping interest. Through the TAM perspective, it was found that perceived usefulness and perceived ease of use are the dominant factors that shape the acceptance of digital payment technology. Meanwhile, through TPB, positive attitudes, subjective norms, and perceived behavioral control were proven to strengthen behavioral intentions to use QRIS consistently. This study also revealed that QRIS adoption has a positive impact on culinary MSMEs through operational efficiency, increased transaction speed, reduced risk of errors, and expansion of the digital consumer market. Overall, QRIS has proven to be a strategic instrument in driving local economic transformation and strengthening an inclusive digital ecosystem in Rambang Port. This research provides theoretical and practical contributions to the development of payment digitalization policies at the regional level.